'And the rest is implementation.' Comparing approaches to what happens in policy processes beyond Great Expectations. (April 2016) - Hupe, Peter L; Hill, Michael J
Implementation occurs as a 'late' part in the stages model of the policy process. As such, it is seen as following upon and subordinate to the preceding stages of agenda-setting and policy formation. Hence, implementation is often addressed as 'the rest'. This view on implementation as a presupposed residual in goal achievement implies little attention to 'political' dimensions, like ambiguity and conflict. Therefore, the view can only partially explain the – sometimes disappointing – results of policy processes. Alternatively, approaches to the policy/implementation nexus with an explicit focus on what happens at the street level have a greater explanatory potential. They are not taking implementation for granted as a seemingly technical matter, simply prescribed by policy objectives.